Studi Pelayanan Publik di Kecamatan Juwana Kabupaten Pati - Heri Cahyono; Endang Larasati; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Based on the study results indicate that the improvement of public services in district Juwana Pati haven't quite successfully, although there are some indicators that are considered very successful, but many more who rated the author less successful. Indicators that have not succeeded is the improvement of service to a maximum of belu since many employees who own a chat either what is discussed, sometimes insufficient peralan lemot, as well as the availability of means of supporting infrastructure.Conclusions in this study is the overall improvement of public services in the Office of District Juwana Pati Subdistrict Office conducted Juwana Pati. A constraint is a restriction on the equipment owned by the insufficient work, lack of participation of employees.Based on the conclusions researchers recommend to the district juwana sub-district starch to fix indicator is less suc